Abstract Guided Inquiry Learning with Mind Mapping and Concept Map to Increase Concept Mastery and Student Learning Motivation - Diah Mustikarini; S. Kurniasih; Prasetyorini Prasetyorini (JSEP (Journal of Science Education and Practice), 2021)
This study aims to measure students' conceptual mastery and motivation in learning the respiratory system. The study was conducted on class VIII SMPN 1 Klapanunggal students in 2017/2018. The learning used in this study was through guided inquiry learning with mind mapping with pretest posttest control group design. The use of this research design involves two classes as research samples, one experimental class and one control class. The selection of these two classes is done by taking subjects not based on strata, random or regional but based on certain goals. The research subjects were divided into two groups, namely the experimental group and the experimental group. control. The experimental group received Guided Inquiry learning with mind mapping, while the control group was the group that received Guided Inquiry learning with concept maps. The results of mastery of the concept of the experimental class and control class each obtained an average gain of 6.09 and 5.78, the average pretest score of the experimental class students was 51.9 and the control class students were 44.7 from the ideal score. This shows that the average pretest score of the two classes is not much different. It can be concluded that the average N-gain in the control class is 36.9% in the medium category, while in the experimental class the average N-gain is 43.7% in the medium category.